Allelopathic potential of Lupinus polyphyllus L. in relation to habitat variables - Milena Powolny; Daniel Pruchniewicz (Ecological Questions, 2026)
Lupinus polyphyllus L. is an invasive species widely spread in Europe. Despite many studies on perennial lupine, relatively few have explored its allelopathic potential. . Hence, the aim of this study was to determine the allelopathic effects of three perennial lupine populations originating from various habitats (lowland – S1, foothill – S2 and mountain – S3) on the growth and development of two target species – white mustard (Sinapis alba L.) and meadow red-fescue (Festuca rubra L.). The goal was to determine which of the habitat factors have the greatest influence on the allelopathic potential of this species. The results of conducted research have not demonstrated the existence of clear dependencies which could allow to determine which populations of perennial lupine have the strongest allelopathic potential to inhibit the seed germination and growth of the target species. Among the analyzed habitat factors in laboratory conditions, low concentrations of phosphorus in the soil can stimulate the production of allelochemicals inhibiting the seed germination of the two target species - S. alba and F. rubra.